(untitled) - Akshay Bhargava (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2021)
Broadband discourse of Jus Cogens by the academic philosophers has been much sharing the similar inference as to the universality of this norm in its applicability in the entire global legal system irrespective of its being experiencing differing ratio of its acceptance on one hand or the rejection at the other. Certainly, the norm of Jus Cogens has never been propounded bearing the intention to cause it a dead letter though there lies a need to ponder upon the relevance of this principle in the contemporary world of emerging global ties between the nations. The major contribution of the present research study is to examine the global impact of Jus Cogens after the development of Vienna Convention and to analyze its relevance in the emergence of new legal challenges in the new world order. Also, present research focuses on analyzing the relevance of Jus Cogens in the implementation of Law of Treaties and its role in the realm of international disputes. The major outcome of the study is the collective consensus of existing literatures on the said subject which provides that the appreciation of the norm of Jus Cogens rests on the symbolic value and the underlined vision of it in the entire international legal system. In this regard, the most suitable and richest suggestions are found significant place in the present study containing the discourse as to the claim regarding the violation of Jus Cogens.